An Exploratory Study of Determinants and Corrective Measures for Software Piracy and Counterfeiting in the Digital Age - Theng, Yin-Leng (2015)
Software piracy and counterfeiting is a global problem that has resulted in huge economic losses worldwide. This paper proposes a theory-based approach to study the key factors contributing to piracy and counterfeiting issues. We first developed a theoretical model linking the antecedents into the key factors using information acquired from an extended literature review. We then undertook a survey of thirty business professionals representing different industries, functional roles and different levels of work exposure to software usages in Singapore to investigate the issues. Specifically, the objectives of the survey were to: (1) investigate the key issues associated to software piracy and counterfeiting; (2) identify the factors that have contributed to the software piracy and counterfeiting; and (3) draw up a refined list of appropriate measures to counter software piracy and counterfeiting. Through the structural use of Non-Parametric Correlation Test, Chi-Square Test for Independence, Fisher Exact Probability Test and Phi value, our findings showed that the lack of awareness to software usage laws and regulations, the perceived lack of enforcement measures and penalties, and the lack of educational programs catering to the proper usage of software were the key factors contributing to the software piracy and counterfeiting issues. The findings are useful to managers of software companies and policy-makers in reviewing existing software protection policies, laws and regulations, such that any flaws or loopholes can be identified.